The role of oxidative stress in Friedreich's ataxia - Lupoli, Federica; Vannocci, Tommaso; Longo, Giovanni; Niccolai, Neri; Pastore, Annalisa (FEBS letters, 2018)
Oxidative stress and an increase in the levels of free radicals are important markers associated with several pathologies, including Alzheimer's disease, cancer and diabetes. Friedreich's ataxia (FRDA) is an excellent paradigmatic example of a disease in which oxidative stress plays an important, albeit incompletely understood, role. FRDA is a rare genetic neurodegenerative disease that involves the partial silencing of frataxin, a small mitochondrial protein that was completely overlooked before being linked to FRDA. More than 20 years later, we now know how important this protein is in terms of being an essential and vital part of the machinery that produces iron‐sulfur clusters in the cell. In this review, we revisit the most important steps that have brought us to our current understanding of the function of frataxin and its role in disease. We discuss the current hypotheses on the role of oxidative stress in FRDA and review some of the existing animal and cellular models. We also evaluate new techniques that can assist in the study of the disease mechanisms, as well as in our understanding of the interplay between primary and secondary phenotypes.